2003
DOI: 10.3310/hta7290
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of diagnostic tests for the assessment of shoulder pain due to soft tissue disorders: a systematic review

Abstract: This monograph may be freely reproduced for the purposes of private research and study and may be included in professional journals provided that suitable acknowledgement is made and the reproduction is not associated with any form of advertising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
196
5
45

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(256 citation statements)
references
References 93 publications
(453 reference statements)
10
196
5
45
Order By: Relevance
“…MRI missed one case of partial thickness tear this may be attributed to absence of joint effusion or presence of granulation tissue or scaring this is in agree with (9) who stated that in the absence of joint effusion, articular surface partial-thickness tears may be difficult to be identified, particularly in the setting of granulation tissue or scarring. In our study both ultrasound and MRI were equally able to detect full thickness rotator cuff tear this is in agree with (8) and (10) who stated that either MRI or sonography could be used for equal detection of full thickness rotator cuff tears. In our study US and MRI was similarly accurate in detection of complete rotator cuff tear, however for partial tear the US appear less accurate than MRI this is in agree with (10) who showed that ultrasonography was accurate as MRI for predicting the full thickness tears but less for moderate and small tears.…”
Section: : Biceps Tendon Lesionssupporting
confidence: 81%
See 1 more Smart Citation
“…MRI missed one case of partial thickness tear this may be attributed to absence of joint effusion or presence of granulation tissue or scaring this is in agree with (9) who stated that in the absence of joint effusion, articular surface partial-thickness tears may be difficult to be identified, particularly in the setting of granulation tissue or scarring. In our study both ultrasound and MRI were equally able to detect full thickness rotator cuff tear this is in agree with (8) and (10) who stated that either MRI or sonography could be used for equal detection of full thickness rotator cuff tears. In our study US and MRI was similarly accurate in detection of complete rotator cuff tear, however for partial tear the US appear less accurate than MRI this is in agree with (10) who showed that ultrasonography was accurate as MRI for predicting the full thickness tears but less for moderate and small tears.…”
Section: : Biceps Tendon Lesionssupporting
confidence: 81%
“…In our study both ultrasound and MRI were equally able to detect full thickness rotator cuff tear this is in agree with (8) and (10) who stated that either MRI or sonography could be used for equal detection of full thickness rotator cuff tears. In our study US and MRI was similarly accurate in detection of complete rotator cuff tear, however for partial tear the US appear less accurate than MRI this is in agree with (10) who showed that ultrasonography was accurate as MRI for predicting the full thickness tears but less for moderate and small tears.…”
Section: : Biceps Tendon Lesionssupporting
confidence: 81%
“…Afeta mais frequentemente o tendão do músculo supraespinoso, na vizinhança da sua inserção com a tuberosidade maior do úmero, imediatamente abaixo do bordo externo do acrómio. A incidência das lesões aumenta com a idade, sendo, no entanto, os microtraumatismos e a sobrecarga profissional e/ou desportiva importantes causas em qualquer faixa etária [1][2][3] . A etiologia da TMR é multifatorial, resultando da combinação de fatores intrínsecos, extrínsecos e ambientais 4 .…”
Section: Introductionunclassified
“…A ultrassonografia (US), além da elevada sensibilidade na identificação de calcificações e de possibilitar guiar procedimentos diagnósticos e/ou terapêuticos invasivos, pode ser utilizada na presença de material pós-operatório metálico e em casos de claustrofobia 21 . Além disso, o baixo custo, a acessibilidade e a inocuidade conferem-lhe vantagens em relação às restantes técnicas de imagem 2,22 que exigem, todavia, experiência do examinador 1,13,[22][23][24][25] . Entre as alterações estruturais mais comuns destacam-se:…”
Section: Introductionunclassified
“…Several excellent reviews and numerous studies have been devoted to identifying work-related MSD risk factors (14)(15)(16)(17)(18), how to assess exposure to these risk factors (19)(20)(21)(22)(23), physiological mechanisms explaining MSD (24,25), effective levels of action (5,26,27), ergonomics effects of changes caused by rationalizations (28), and outcomes of interest to ergonomics interventions such as health (29,30) and profitability (31)(32)(33). While these issues are central to the understanding of how to design an effective intervention, they do not address the process of change per se.…”
mentioning
confidence: 99%